Adolescent cannabis use, depression and anxiety disorders in the Northern Finland Birth Cohort 1986 - Mustonen, Antti; Hielscher, Emily; Miettunen, Jouko; Denissoff, Alexander; Alakokkare, Anni-Emilia; Scott, James G.; Niemelä, Solja (BJPsych Open, 2021)
Background Cannabis use has been associated with increased risk of psychiatric disorders. However, associations between adolescent cannabis use, depression and anxiety disorders are inconsistently reported in longitudinal samples. Aims To study associations of adolescent cannabis use with depression and anxiety disorders. Method We used data from the Northern Finland Birth Cohort 1986, linked to nationwide registers, to study the association between adolescent cannabis use and depression and anxiety disorders until 33 years of age (until 2018). Results We included 6325 participants (48.8% male) in the analyses; 352 (5.6%) participants reported cannabis use until 15–16 years of age. By the end of the follow-up, 583 (9.2%) participants were diagnosed with unipolar depression and 688 (10.9%) were diagnosed with anxiety disorder. Cannabis use in adolescence was associated with an increased risk of depression and anxiety disorders in crude models. After adjusting for parental psychiatric disorder, baseline emotional and behavioural problems, demographic factors and other substance use, using cannabis five or more times was associated with increased risk of anxiety disorders (hazard ratio 2.01, 95% CI 1.15–3.82), and using cannabis once (hazard ratio 1.93, 95% CI 1.30–2.87) or two to four times (hazard ratio 2.02, 95% CI 1.24–3.31) was associated with increased risk of depression. Conclusions Cannabis use in adolescence was associated with an increased risk of future depression and anxiety disorders. Further research is needed to clarify if this is a causal association, which could then inform public health messages about the use of cannabis in adolescence. Peer reviewed